Dinâmica temporal da comunidade de amebas testáceas em uma planície de inundação Neotropical : traços funcionais e potencial bioindicador das condições ambientais. - Schwind, Leilane Talita Fatoreto (2016)
Understanding the regulatory factors that influences the structuring and establishment of communities has been common in ecological studies. This thesis had as a research area lakes of the upper Paraná River floodplain. In the first approach of this thesis, we evaluate the influence of hydrological periods on the convergence and divergence of functional traits of testate amoebae in a long period of time. There was a predominance of convergence of functional traits in flooding and divergence in the drought. Furthermore, the functional traits were strongly influenced by the temporal changes of the environmental variables linked to the food resources. In the second approach, we verified the effect of temporal variation in the productivity variables on testate amoebae community in the studied floodplain lakes. We seek also to identify taxa indicators increase and decrease the concentrations of these variables over time. The temporal variation influenced the productivity of variables, the frequency and abundance of testate amoebae community, alternating the establishment of taxa. As a result, it was possible to identify indicator species of increase and decrease the concentrations of these environmental variables. In summary, the results of this thesis contributed to the knowledge of the testate amoebae ecology in aquatic environments, considering that addressed the distribution of functional traits of these organisms and their potential bioindicator aquatic ecosystems.